Refleksi Orientasi Pendidikan Islam Berbasis Kecerdasan Profetik: Studi di Pondok Pesantren Puncak Darussalam Pamekasan - Ali Makki; Abu Siri; Syukron Khalil (Aqlamuna: Journal of Educational Studies, 2023)
The orientation of Islamic education generally refers to two directions of interest, namely serving Allah SWT and understanding humans as caliphs on earth with various kinds of duties and responsibilities. The focus of this research is prophetic intelligence in growing the potential of Islamic life through the orientation of Islamic education at the Puncak Darussalam Islamic Boarding School and maintaining a good balance of relationships between individual intelligence (Intelligence Quotient), emotional intelligence (Emotional Quotient) and spiritual intelligence (Spiritual Quotient) which is prophetic. The figure of the Prophet Muhammad SAW as uswah hasanah or the best role model for mankind. This research uses a descriptive qualitative approach with a single case study type. The important findings of this research are: (a) the growth of the potential for students' Islamic life and an environment based on prophetic intelligence (b) the maintenance of a good, balanced relationship between humans and their God as caliph on earth. These findings indicate the importance of Islamic boarding schools responding positively in managing students and their environment in accordance with the orientation of Islamic education and the Islamic boarding school's vision and mission